2001
DOI: 10.1002/1522-2675(20010919)84:9<2813::aid-hlca2813>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Behavior of the Dual Fluorescence of 2-(3-Fluorophenyl)-2,3-dihydro-1H-benzo[f]isoindole-1,3-dione

Abstract: Dedicated to Prof. Andre M. Braun on the occasion of his 60th birthdayThe fluorescence behavior of 2-(3-fluorophenyl)-2,3-dihydro-1H-benzo[f]isoindole-1,3-dione (1) was studied in solvents of different polarity and viscosity. Dual luminescence is observed and the short-wavelength emission is found to increase considerably with the solvent polarity. The ratio of the fluorescence quantum yield of the two states emitting, the one (SW*) at short wavelength and the other (LW*) at long wavelength, shows a bell-shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Furthermore, the decrease of the temperature increases significantly the polarity of the medium. 11 We have found recently 12 that the ratio of the SW* and LW* state fluorescence quantum yields of N-(3-fluoro-phenyl)-2,3-NI 2 varies with the temperature as a result of an energy barrier between the two excited states. Therefore, the experiments have been carried out at constant temperature, in order to limit our study to the sole influence of the viscosity of the medium.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the decrease of the temperature increases significantly the polarity of the medium. 11 We have found recently 12 that the ratio of the SW* and LW* state fluorescence quantum yields of N-(3-fluoro-phenyl)-2,3-NI 2 varies with the temperature as a result of an energy barrier between the two excited states. Therefore, the experiments have been carried out at constant temperature, in order to limit our study to the sole influence of the viscosity of the medium.…”
Section: Introductionmentioning
confidence: 99%
“…As a model of dual luminescent compounds, N-(3-fluorophenyl)-2,3-naphtalimide (MFPN) (where the LE → ICT reaction is reversible [6,7]) and N-(4-methoxyphenyl)-2,3naphtalimide [4] (PMPN) (where the ICT state has clear intramolecular charge transfer character [4]) were selected.…”
Section: Introductionmentioning
confidence: 99%
“…Arene-dicarboximides show interesting photochemical and photophysical properties, such as photoreduction [1,2] photocycloaddition [3,4], and photo-excited emission [5][6][7][8]. Heagy et al reported that dual fluorescent naphthalene-2,3dicaboximides could be used in white organic light-emitting devices (OLEDs) [9].…”
Section: Introductionmentioning
confidence: 99%
“…We have applied our improved method to synthesize the title heterocyclic com pounds. In this paper, we describe the synthesis of the 1,3-diarylisobenzofuran-5,6-dicarboximides (6)(7)(8) and their A solution of 2,5-diaryl-3,4-bis(methoxycarbonyl)furan (19.0 mmol) in 70 mL of THF was added slowly to a suspension of 1.14 g of LiAlH 4 (30.0 mmol) in 50 mL of THF at 0ºC. After being stirred at room temperature for 30 h, the reaction mixture was carefully quenched by ethanol/water.…”
Section: Introductionmentioning
confidence: 99%